Economic activity and patterns of infant growth in a high altitude district of Peru. Issue 6 (16th July 2017) - Hoke, Morgan K.
Abstract: Objectives: Changing economic activities bring significant cultural, epidemiological, and nutritional transitions. Infancy represents a critical period when rapid growth and metabolic programming occur, making infants particularly vulnerable to long‐lasting biological changes due to such transitions. This paper examines the relationship between residence in distinct economic production zones (urban, herding, and dairy) and early growth in a highland district of Peru. Methods: The length, weight, body mass index, and triceps skinfold of 93 infants (55 boys and 38 girls, aged 2 to 24 months) from 3 economic zones were measured at two time points 6 months apart. Z ‐scores were calculated based on the WHO Growth Reference for children under 5 years of age. Comparisons were made to the reference group and between economic zones to examine the impacts of different economic activities on infant growth. Results: Female infants had significantly higher height‐for‐age z‐scores (HAZ) than males ( P < 0.05). Across zones, dairying infants had the highest HAZ scores and the lowest prevalence of stunting. There was a significant association between zone and HAZ at baseline. While these associations were attenuated in measurements, taken 6 months later, longitudinal growth monitoring revealed differential patterns of weight gain and adiposity deposition across the zones with herding infants showing consistent high adiposity and urban infants gaining both weight and adiposity between rounds. Discussion: Changes in economic activity are bringing about nutritional and epidemiological transitions in the Nuñoa district. Economic activity is a key factor influencing early growth with distinct longitudinal growth patterns in each economic zone.